Anhedonia and depression severity measures during ketamine administration in treatment-resistant depression - Kwaśny, Aleksander; Cubała, Wiesław Jerzy; Włodarczyk, Adam (Frontiers in Psychiatry, 2024)
Background Anhedonia is a core symptom of depression characterized by a diminished ability to experience pleasure. Currently available treatments for depression often fall short in adequately addressing anhedonia that often presents as a chronic and debilitating symptom. Ketamine is known to possess antianhedonic properties. Methods This post-hoc analysis of a naturalistic observational study of treatment-resistant depression inpatients (n=28) analyzed antianhedonic response patterns measured by Snaith-Hamilton Pleasure Scale and changes in Inventory of Depressive Symptomatology in responders (n=6) and non-responders (n=22) stratified per Montgomery-Åsberg Depression Rating Scale during short-term ketamine treatment. Results Results show that responders significantly improve in anhedonia over time (p=0.0084) and at the 7th infusion and follow-up (both p<0.05). Non-responders reported significant reduction in anhedonia over time (p=0.0011) and at the 5th, 7th infusion and at the follow-up (all p’s<0.05). Non-responders were also observed to improve significantly in self-reported depression at the 7th infusion (p=0.0219) but not at the follow-up. Discussion There is no complete overlap between change in depressive symptoms and anhedonia. Therefore, it might be assumed ketamine alleviates anhedonia as an individual symptom domain regardless of formal treatment outcome.